Pengaruh Model Problem Based Learning Materi Taharah Pada Prestasi Belajar Peserta Didik Kelas VII Di SMPN 2 Kepung - Durrotul Lami'ah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
paradigm shift in the learning process. Its implementation in the 2013 curriculum, educators are in the position of facilitators. But in reality, educators are still a source of knowledge. Based on the results of interviews with religious teachers at SMPN 2 Kepung, it is known that religious learning in grades VII H and VII I is still using the direct instruction learning model. With this learning model, students participate less in learning activities. This of course causes students to be passive. So that less active learning results in low student motivation to learn. This research is a quantitative research using the True Experimental Post-test only Control Group Design method. The population in this study were all seventh grade students at SMPN 2 Kepung. The sample in this study used purposive sampling, totaling 76 children from two VII grades. Data collection techniques using tests and documentation. As for the analysis of research data using SPSS 21.